Correction to: Use of multicolor fluorescence in situ hybridization to detect deletions in clinical tissue sections. (June 2018) - Yoshimoto, Maisa; Ludkovski, Olga; Good, Jennifer; Pereira, Ciro; Gooding, Robert; McGowan-Jordan, Jean; Boag, Alexander; Evans, Andrew; Tsao, Ming-Sound; Nuin, Paulo; Squire, Jeremy
Figure 2 is incorrect in the original version of this article. The correct figure 2 is provided below